Kontribusi Akad Syirkah Dalam Pembangunan Ekonomi dan Kebahagian Ummat - Adawiyah, Robiyatul; Faizal Nurmantias (Institut Agama Islam Tafaqquh Fiddin Dumai, 2021)
The goal of development in an Islamic economic perspective is the creation of prosperity both in the world and in the hereafter; prosperity in the world is marked by the fulfillment of all the necessities of life. Based on BPS data, it is known that in 2022 the unemployment rate in Indonesia will be 5.86%. Meanwhile, it is also known that Indonesia has the largest Muslim population. This study aims to determine the contribution of the syirkah contract to the ummah's economy. This study used qualitative research methods, data were collected using library research methods and then data were analyzed using descriptive qualitative analysis. The results of the study show that if a syirkah contract is carried out in accordance with the rules described in the Qur'an and Hadith and pays attention to its benefits, it will contribute to prosperity.